The peculiarities of stochastic heating of the plazma in plasma resonator - Antonov, A.N.; Buts, V.A.; Kovalchuk, I.K.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G.; Tarasov, D.V.; Scherbina, A.N. (Вопросы атомной науки и техники, 2014)
The results of the investigation of the dynamics of particles and waves at the interaction of intense electromag-netic pulses with plasmas are presented. It is shown that under conditions when regimes with dynamic chaos for wave-particle and wave-wave interactions are realized, there are still some correlation processes. They occur in the appearance of electromagnetic bursts that occur after sufficiently long time after the pulse, which acts on the plasma. In addition, the shape of instantaneous spectra of oscillations in plasma has a line structure.